VARIASI MORFOLOGI Macrobrachium idae ASAL SUNGAI KAWUNG KABUPATEN BANYUMAS DAN SUNGAI LUK ULO KABUPATEN KEBUMEN (MORPHOLOGY VARIATIONS OF Macrobrachium idae TAKEN FROM KAWUNG RIVER IN BANYUMAS REGENCY AND LUK ULO RIVER IN KEBUMEN REGENCY) - Winarni, Elly Tuti; Pulungsari, A.E; , Kusbiyanto (Pembangunan Pedesaan, 2011)
Many researches on Macrobrachium shrimp in Indonesia focus more on Macrobrachium osenbergii, because other Macrobrachium shrimps are smaller, including M. idae. The previous study howed that M. idae spread widely as it could be found in the rivers, but the number and the size were elatively small. Possibly in the future, the existence of this shrimp cannot be found anymore, so the prevention has to be conducted through biological and ecological scientific information. As a preliminary, a biological study is carried out to see the morphological characteristics of M. idae shrimp with the purpose of knowing the differences between the shrimps taken from Kawung river in Banyumas regency and Luk Ulo river in Kebumen regency. This information can be used as a foundation of other researches aims at conserving M. idae shrimps. This research used a survey method with a simple random sampling. Variables observed were color design and truss distance. There were 21 characteristics of truss to figure out the shape of the whole body. The measurement of truss ratio compared to the standard length of the shrimp was analyzed using t test. The result showed that male M. idae shrimp had a bigger size than that of the female one. There was a different color design and 2 truss ratio distance in comparison to the length standard, between M. idae taken from Kawung and Luk Ulo rivers.